Employees’ perception towards Green HRM practices in Indian Power Sector-A case Study of Damodar Valley Corporation - Chandan Kumar , Saikat Kumar Kar ,Dibakar Bose , Dr Kaushik Banerjee , Dr Kaushik Banerjee (International Journal of Advanced Science and Technology, 2020)
The corporate world is changing the perspective from a business oriented financial perspective to a competency based economy and green economy. Its aim is to increase the awareness among the employees on the issue of sustainability